2017
DOI: 10.1021/acschembio.7b00851
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Chemical Biology of Desferrioxamine B

Abstract: Desferrioxamine B (DFOB) was discovered in the late 1950s as a hydroxamic acid metabolite of the soil bacterium Streptomyces pilosus. The exquisite affinity of DFOB for Fe(III) identified its potential for removing excess iron from patients with transfusion-dependent hemoglobin disorders. Many studies have used semisynthetic chemistry to produce DFOB adducts with new properties and broad-ranging functions. More recent approaches in chemical biology have revealed some nuances of DFOB biosynthesis and discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 164 publications
1
60
0
Order By: Relevance
“…The exquisite affinity of 1 for Fe III (log K a =31) supports its use either as a single agent, or more often in combination therapy, for secondary iron overload disease in people with transfusion‐dependent blood disorders . The solvent‐exposed primary amine group in 1 is not involved in Fe III coordination and is amenable to labeling, as demonstrated by the production of a range of derivatives by means of semisynthetic chemistry …”
Section: Introductionmentioning
confidence: 99%
“…The exquisite affinity of 1 for Fe III (log K a =31) supports its use either as a single agent, or more often in combination therapy, for secondary iron overload disease in people with transfusion‐dependent blood disorders . The solvent‐exposed primary amine group in 1 is not involved in Fe III coordination and is amenable to labeling, as demonstrated by the production of a range of derivatives by means of semisynthetic chemistry …”
Section: Introductionmentioning
confidence: 99%
“…5) is produced by V. cholerae (98). An extensive review of polyamine-containing siderophores and other natural products is not possible in this minireview, but it is worth mentioning the analytical chemical and biochemical tour de force by Codd et al (99,100) that revealed the biosynthetic sequence of the linear and cyclic diamine-based desferrioxamine-type siderophores.…”
Section: Polyamine-based Siderophoresmentioning
confidence: 99%
“…Pharmaceutics 2020, 12, x FOR PEER REVIEW 5 of 13 The 8-arm-PEG-DFO conjugates were synthesized by coupling DFO to an 8-arm-PEG with a mean molecular weight of 20 kDa or 40 kDa, respectively ( Figure 1). 1 HNMR was used to ensure the synthesis of the 8-arm-PEG-DFO conjugates (Figure 2A). In the spectrums of conjugates, the newlyappeared conjugate peak at 7.75 ppm was assigned to the amido bonds, indicating the conjugation of DFO to the 8-arm-PEG macromolecules.…”
Section: The Synthesis and Characterization Of 8-arm-peg-dfo Conjugatesmentioning
confidence: 99%
“…Chelation therapy has been widely used in the treatment of iron overload, especially when the patients received a regular blood transfusion, such as for thalassemia [1,2]. Blood transfusion adds to the iron burden in patients with high risk of the damage of the liver, endocrine system, and heart.…”
Section: Introductionmentioning
confidence: 99%